FACTORS AFFECTING THE SUCCESS OF REGIONAL DEVELOPMENT BANK (BPD) TRANSFORMATION IN INDONESIA IN 2024 - Firman Iswahyudi Mustopo; Budiyanto Budiyanto; Solimun Solimun (AIBPM Publisher, 2019)
The transformation program of Regional Development Bank (BPD) was created to overcome its problems. The success of the transformation of Regional Development Bank is influenced by several factors. This paper discusses several factors that are thought to influence the transformation of BPD, namely: regional economic growth, learning and growth perspective, nation's culture, organizational culture, public policy, bank health level, regional autonomy (Otoda), BPD leadership style, and BPD sustainable competitive advantage. The results of the study show that the factors that significantly influence the success of BPD Transformation in Indonesia in 2024 are learning and growth perspective, nation’s culture, organizational culture, public policy, bank health level, regional autonomy and BPD sustainable competitive advantage. The nation’s culture variable acts as the strongest driver and BPD sustainable competitive advantage variable is the strongest obstacle to the success of BPD transformation in Indonesia in 2024.